A Diagnostic Role Of Fine Needle Aspiration Cytology And Its Histopathological Correlation In Malignant Breast Lesions (Indian Journal of Applied-Basic Medical Sciences, 2020)
BACKGROUND: Breast lesions in women are most common, which require pathological confirmation by FNAC and  histopathological correlation. Recent approach to breast masses is to get cytopathological diagnosis before  surgery.  Aim of study: To study the diagnostic role of Fine Needle Aspiration Cytology and its histopathological correlation in Malignant  breast lesions.  METHOD: The study was conducted in department of pathology; AMC MET Medical College, Maninagar, Ahmedabad,  Gujarat, India, for duration of 1 year from January 2019 to December 2019. During the study period, 40 cases  of fine needle aspiration cytology of malignant breast lesions were performed. Formalin fixed (10%), resected  specimens were received and were prepared for histopathological diagnosis. The cytological and  histopathological slides were stained, studied, analyzed and correlated.  RESULT: During the study period 918 FNAC were undertaken of which 40 FNAC were of malignant breast lesions.  Correlation of FNAC with histopathologic tissue was possible in 20 cases, for which FNAC data was available.  99% were from female and 01% was from male patients. The age of patient ranged from 26 to 95 Years. CONCLUSION: FNAC is useful in diagnosing malignant breast lesions, as this procedure is easy, cost effective and less time  consuming.
Keywords: Cyto-histological correlation; carcinoma breast; fine needle aspiration